PEMBATALAN UANG MUKA DALAM PERJANJIAN PESANAN MENURUT HUKUM EKONOMI SYARIAH (Studi Kasus pada Mebel Jati Ukir Sumber Anugrah Metro Utara) - Zulaikha, Siti (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2018)
Buying and selling is one form of activity that involves the relationship between humans to meet their daily needs. The problems that occur in the order agreement in Mebel Jati Ukir Sumber Anugrah Metro Utara are the practice of applying advances in order agreements and how the views of sharia economic law apply to the cancellation of advances in order agreements. The purpose of this study is to find out how to apply advances in agreements order and know how the views of sharia economic law on the application of advances in the agreement of orders for Mebel Jati Ukir Sumber Anugrah Metro Utara. The benefit of this study is to be able to add to the scientific repertoire in the field of muam especially regarding the views of sharia economic law on the application of advances in order agreements and as input for the people who make order agreements to pay attention to Islamic economic law provisions so that no party is harmed. This study uses a type of field research research with the nature of qualitative descriptive research. Data sources used are primary data sources and secondary data sources. The data obtained were analyzed using qualitative analysis methods namely inductive methods. Based on the research it can be concluded that the application of advances in the order agreement in teak Mebel Jati Ukir Sumber Anugrah Metro Utara according to Sharia Economic Law is permissible. This is because the furniture owner has provided a period of time for the buyer to settle the remaining payment. So that if the buyer cannot pay off the remaining payment before maturity, then the advance that has been given belongs to the furniture.